(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Scoliosis is one of the most common diseases of the musculoskeletal system among adolescents, which is characterized by progressive curvature of the spine in the frontal plane, impaired body biomechanics and functions of internal organs. Physical therapy is the main direction of conservative treatment of scoliosis, which is aimed at correcting spinal curvature, strengthening the muscle corset and preventing the progression of deformities. Purpose of the study: to theoretically substantiate the features of the use of manual therapy in physical therapy of adolescents with scoliosis. Research methods. The work used methods of the theoretical level of research: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodological literature. Results of the work. Elements of manual therapy, in particular mobilization and soft techniques, are gaining increasing importance in modern physical therapy as methods that allow influencing not only the spine, but also the associated muscular and fascial structures. They contribute to improving spinal mobility, reducing muscle tension, restoring balance in the musculoskeletal system and improving postural control. The use of manual therapy in combination with traditional physical therapy methods has the potential to improve the effectiveness of treatment of adolescents with scoliosis. Manual therapy is an effective component of conservative treatment of adolescent idiopathic scoliosis, complementing standard physical therapy methods. It is aimed at reducing muscle spasm, improving spinal mobility and restoring the biomechanical balance of the spinal motor segment. Conclusions. The effectiveness of manual therapy depends on the individual characteristics of the patient, such as age, degree of curvature, skeletal maturity and functional state of the spine. This requires a personalized approach to planning therapeutic interventions.